Recombinant urokinase for restoration of patency in occluded central venous access devices - Haire, William D.; Deitcher, Steven R.; Mullane, Kathleen M.; Jaff, Michael R.; Firszt, Carolyn M.; Schulz, Gregory A.; Schuerr, Debra M.; Schwartz, Lewis B.; Mouginis, Tamyra L.; Barton, R. Phillip (Thrombosis and Haemostasis, 2004)
The interval occlusion of central venous access devices (CVADs) remains a significant clinical problem, often requiring re-intervention for catheter exchange or replacement.The purpose of this Phase 3, multi-center, double-blinded study was to test the hypothesis that instillation of recombinant urokinase (r-UK) 5000 IU/ml is superior to placebo in restoring total catheter patency to an unselected cohort of occluded CVADs. After obtaining informed consent, adult and pediatric patients with occluded, non-hemodialysis CVADs of any duration or type were randomized (2 : 1) to receive either r-UK 5000 IU/ml or placebo instilled into all occluded lumens of their catheter. Catheter function was assessed at 5, 15 and 30 min after the first instillation. If the catheter remained occluded after 30 min, a second dose was instilled with repeat assessments at 5, 15 and 30 min.The primary efficacy variable was the restoration of catheter function to all treated lumens (i.e., total catheter patency) after one or two instillations. Catheters that were not successfully recanalized after two instillations were allowed to receive up to two instillations of open-label r-UK administered in the same manner.The primary safety variable was the occurrence of hemorrhagic and non-hemorrhagic events within 72 hr after instillation. A total of 180 patients were enrolled at 43 sites in the United States and Canada. Most patients were adults, although 20% were ≤18 years of age. CVAD types included totally implanted subcutaneous ports (45%), PICC lines (26%), non-tunneled percutaneous catheters (18%), and tunneled percutaneous catheters (10%). All CVADs were occluded by virtue of their inability to withdraw blood (withdrawal occlusion). Additionally, 32% of catheters were completely dysfunctional as blood could not be withdrawn and fluids could not be infused (total occlusion). Analysis of the results showed that r-UK was significantly better than placebo in restoring catheter function (54% versus 30%, p = 0.002). There were no major hemorrhagic events within 72 hr after up to four r-UK instillations, and the incidence of non-hemorrhagic events was similar among the r-UK and placebo groups. In conclusion, r-UK is superior to placebo in restoring total catheter patency to occluded CVADs. In patients with occluded CVADs, intra-catheter thrombolysis can restore patency and may obviate the need for catheter replacement.
Keywords: Urokinase; central venous catheter; thrombolysis